The betrayal knows my name. [Vol. 3] - Odagiri, Hotaru (Yen, 2012)
"Finally learning more from Takashiro abut the "Sunset of the Underworld" that took place a thousand years past, Yuki finds his thoughts returning once again to his former-friend-turned-nemesis, Kanata... But while in his current incarnation Yuki may be new to picking sides in a centuries-old war, it is nothing new to the collective Zweilt. Kuroto and Senshirou in particular are a pair driven by the seething hatred they harbor for the Duras and one Opast in particular. What happened four years ago to inspire such intense loathing in two otherwise reasonable individuals? As Yuki bears witness to the flames of revenge that burn in the hearts of those around him, how will his own heart respond to the betrayal he cannot forget?"--P. [4] of cover.